2015
DOI: 10.1177/0142331215619973
|View full text |Cite
|
Sign up to set email alerts
|

Smith predictor based sliding mode control for a class of unstable processes

Abstract: A strategy to regulate unstable processes using a modified Smith predictor based sliding mode controller (SP-SMC) is illustrated. The proposed scheme presents disturbance rejection and optimal control input usage with overall improved regulatory performances. The unstable process with time delay is first estimated using a simple measurement of limit cycle output obtained from a modified relay experiment. Then this paper extends a work on SP-SMC for unstable processes, which leads to significant improvements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…A similar switching function, which delivered a potential advantage for unstable processes with dead times, was presented in [22] as well.…”
Section: Smith Predictor With Sliding Modementioning
confidence: 93%
See 1 more Smart Citation
“…A similar switching function, which delivered a potential advantage for unstable processes with dead times, was presented in [22] as well.…”
Section: Smith Predictor With Sliding Modementioning
confidence: 93%
“…The robustness to parameter variation and disturbance rejection was shown to be improved compared to the original structure of SP [18]. This structural technique was further improved for unstable processes [22] using power rate reaching law and the metaheuristic optimization algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing or decreasing γ allows one to modify the weight on the manipulated variable; for instance, when γ = 1, both, the IAE and IMV are of the same importance, and when γ = 0 only the IAE is considered. Several authors have used this type of objective function in order to measure the performance of different control strategies [50,51]; typical values of the suppression factor are 0 ≤ γ ≤ 8 [52,53].…”
Section: Optimization Objective Functionmentioning
confidence: 99%
“…But, conventional Smith predictor [3] technique fails to perform satisfactorily for integrating processes with large dead time due to their inherent nonself-regulating nature. Over the last few decades, a decent amount of research findings are reported [4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24][25] towards modification and augmentation of the conventional Smith predictor [3]. Primarily Majhi and Atherton [11] proposed modified Smith predictor for integrating and unstable processes based on gain margin and phase margin criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Although modified Smith predictor for second-order process with non-minimum phase using two controllers is proposed by Uma and Rao [23] signifies enhanced responses for unstable processes. Alternative approach towards modified Smith predictor with sliding mode control for processes with large time delay is provided by Mehta and Kaya [24], and the similar strategy for unstable processes is also proposed by Mehta and Rojas [25]. Among these reported schemes [8,9,11,19,[21][22][23][24][25] majority of the modified Smith predictor mechanism involves three controllers and their tuning policy is also not quite straight forward in nature.…”
Section: Introductionmentioning
confidence: 99%